Tribological and thermal investigation of modified hot stamping tools - Neubauer, Franziska; Merklein, Marion (Tribology in Industry, 2019)
Direct hot stamping is an established manufacturing process to produce safety-relevant car body components, while t-he hot blank is formed and quenched simultaneously in a water cooled press. In order to protect the semi-finished parts against oxidation the surfaces are coated with aluminum silicon. As a side effect this coating system leads to adhesive wear on the tool surface, which reduces the tool life. Due to the high temperatures it is not possible to use lubricants as wear protection. For this reason a suitable surface modification for hot stamping tools is required to increase the wear resistance. In the scope of this study the tribological behavior of different modificatiosn is investigated. The main purpose of these wear protective layers is to decrease the adhesive wear on the tool surface. The wear characterization is carried out with a modified pin-on-disc test. During the experiments the pin is guided over the blank with a robot system. In addition, the contact area is cooled after each wear track to simulate the thermal alternating stresses of the hot stamping process. For the evaluation of the wear behavior a new developed analysis method is used, which enables the calculation of the adhesive and abrasive wear volume.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Alloying; Coatings; Hot stamping; Wear